(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
There is a large number of treatment types offered to parents of children diagnosed with autism spectrum disorders (ASD), but they are particularly vulnerable to the promoters of pseudoscience, which can lead to the use of ineffective types of treatment. This study represents an attempt to document the types of treatments used by parents of children with ASD in the Republic of Serbia. Secondary aim was to determine if certain parent or child characteristics influenced the types of treatments used. Modified version of survey constructed and conducted by Green, et al. (2006) was used. Nearly all (n=85) of the 86 treatments listed in our survey were being currently used or used in the past by at least one parent and the most commonly used treatment is speech and language therapy. The treatments were grouped into ten categories and the most commonly used is other treatments (80.6%), followed by standard therapies (79.2%) and vitamin supplements (65.3%). It is also of great importance to educate the parents of children with ASD about evidence-based treatments and on how to distinguish them from treatments that do not have empirical